2018
DOI: 10.1093/humrep/dey094
|View full text |Cite
|
Sign up to set email alerts
|

When does germ cell loss and fibrosis occur in patients with Klinefelter syndrome?

Abstract: This project was funded by the scientific Fund Willy Gepts from the UZ Brussel (D.V.S., J.D.S.), grants from the Vrije Universiteit Brussel (E.G.) and a Methusalem grant (K.S.). D.V.S is a post-doctoral fellow of the Fonds Wetenschappelijk Onderzoek (FWO; 12M2815N). No conflict of interest is declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 43 publications
5
80
1
6
Order By: Relevance
“…KS is associated with hypogonadism and infertility with fewer than half of adult men reported to have spermatozoa present in the ejaculate, although residual foci with spermatogenesis may be present in some individuals with apparent azoospermia [134]. The testicular phenotype of KS involves a progressive loss of spermatogonial stem cells (SSC) beginning in prepuberty, with testicular fibrosis occurring in (peri)pubertal and adult patients [135]. A meta-analysis of the presence of spermatogonia in individuals with KS demonstrated spermatogonia in the testes of all fetal/infantile samples, 83% of those obtained from prepubertal patients, and in 40-50% of adolescent/adult individuals [20].…”
Section: Klinefelter Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…KS is associated with hypogonadism and infertility with fewer than half of adult men reported to have spermatozoa present in the ejaculate, although residual foci with spermatogenesis may be present in some individuals with apparent azoospermia [134]. The testicular phenotype of KS involves a progressive loss of spermatogonial stem cells (SSC) beginning in prepuberty, with testicular fibrosis occurring in (peri)pubertal and adult patients [135]. A meta-analysis of the presence of spermatogonia in individuals with KS demonstrated spermatogonia in the testes of all fetal/infantile samples, 83% of those obtained from prepubertal patients, and in 40-50% of adolescent/adult individuals [20].…”
Section: Klinefelter Syndromementioning
confidence: 99%
“…Furthermore, the underlying testicular and germ cell abnormalities in individuals with KS may result in additional challenges for the use of this approach for fertility preservation. Therefore, this approach has recently been called into question [135] and testicular tissue cryopreservation in prepubertal patients should only be considered as part of an ethically approved research study.…”
Section: Klinefelter Syndromementioning
confidence: 99%
“…Thus, from a fertility point of view, it should be noted that infertility is common and that less than half of the adult men reported by Corona et al [68] had sperm in their ejaculation, although, in some individuals with apparent azoospermia, there may be residual foci with spermatogenesis. Van Saen et al [69] reported that there is a progressive loss of spermatogonial stem cells that begins at prepubertal time, with frequent testicular fibrosis by adulthood. A meta-analysis of the presence of spermatogonia in individuals with KS demonstrated their presence in the testes of all fetal/infant samples, in 83% of those obtained from prepubertal patients, and in 40-50% of adolescents/adults [70].…”
Section: Klinefelter Syndrome (Ks)mentioning
confidence: 99%
“…However, the underlying abnormalities in the testes and germ cells of individuals with KS may create additional challenges for the use of this approach for fertility preservation. Thus, this approach has recently been questioned [69], and cryopreservation of testicular tissue in prepubertal patients should only be considered as part of an ethically approved research study [41].…”
Section: Klinefelter Syndrome (Ks)mentioning
confidence: 99%
“…Furthermore, pre-existing impairment to the testicular somatic environment of the recipient testis may prevent further germ cell development. Similarly, for patients with Klinefelter syndrome, apparent loss of germ cells has been reported prior to puberty, with the appearance of fibrosis in peri-puberty (Van Saen et al 2018). An overall reduction in spermatogonial numbers have also been reported in peripubertal testes from Klinefelter patients compared to controls (Heckmann et al 2018).…”
Section: Pre-existing Testicular Pathologymentioning
confidence: 86%